2015
DOI: 10.1002/ceat.201400606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overall Gas‐Phase Mass Transfer Coefficient for CO2 Absorption between Tertiary Amines in a Randomly Packed Column

Abstract: The mass transfer performance of CO 2 absorption into an innovative tertiary amine solvent, 1-dimethylamino-2-propanol (1DMA2P), was investigated and compared with that of methyldiethanolamine (MDEA) in a packed column with random Dixon-ring packing. All experiments were conducted under atmospheric pressure. The effects of inert gas flow rate, amine concentration, liquid flow rate, CO 2 loading, and liquid temperature on mass transfer performance were analyzed and the results presented in terms of the volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The turbulence increases in the gas phase because an increase in the gas ow rate can lead to an increase of K GCO 2 a V . 60,77,78 However, experiments by many researchers, which were pointed out in previous sections, differed from the above-mentioned prediction by Fu, et al 60 and Chen, et al 78 works. They showed that the liquid lm could control the process of CO 2 absorption in an amine solution and, as a result, K GCO 2 a V in such a system is unaffected by the gas ow rate.…”
Section: Gas Ow Ratementioning
confidence: 80%
See 2 more Smart Citations
“…The turbulence increases in the gas phase because an increase in the gas ow rate can lead to an increase of K GCO 2 a V . 60,77,78 However, experiments by many researchers, which were pointed out in previous sections, differed from the above-mentioned prediction by Fu, et al 60 and Chen, et al 78 works. They showed that the liquid lm could control the process of CO 2 absorption in an amine solution and, as a result, K GCO 2 a V in such a system is unaffected by the gas ow rate.…”
Section: Gas Ow Ratementioning
confidence: 80%
“…In addition, they showed that by increasing the CO 2 loading for the three mentioned systems, the K GCO 2 a V values decreased. Following the study of Liang, et al, 44 Wen, et al 77 obtained the K GCO 2 a V values in an absorber column packed with Dixon rings for 1DMA2P-CO 2 system. They compared the K GCO 2 a V values for 1DMA2P-CO 2 with those for the MDEA-CO 2 system, and found that the K GCO 2 a V values of the new amine solution were higher compared with the MDEA solution.…”
Section: K Gco 2 Amentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 absorption using an aqueous amine solution is the most established, widely implemented method in the industry, and is considered the main process to reduce CO 2 emissions due to its higher absorption rate and efficiency in diluted gas streams compared to other technologies 4–7 . The drawback of this technology is the high energy consumption required to regenerate the solvent, which usually occurs at its boiling temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of mixtures of amines to improve carbon dioxide absorption has been described in a number of papers, but the conclusions are not clear as to the role of the second amine present in the solvent. Generally a tertiary amine is used as an additive to obtain better results with regards to carbon dioxide loading and/or regeneration degree . The use of a mixture of amines can produce undesirable effects such as an increase in viscosity due to interactions between unlike molecules that causes a decrease in the mass‐transfer rate.…”
Section: Introductionmentioning
confidence: 99%